Fatal Events in Cancer Patients Receiving Anticoagulant Therapy for Venous Thromboembolism. Issue 32 (August 2015) - Farge, Dominique; Trujillo-Santos, Javier; Debourdeau, Philippe; Bura-Riviere, Alessandra; Rodriguez-Beltrán, Eva Maria; Nieto, Jose Antonio; Peris, Maria Luisa; Zeltser, David; Mazzolai, Lucia; Hij, Adrian; Monreal, Manuel; Alessandro, Durante.
<x xml:space="preserve">Abstract</x> Abstract In cancer patients treated for venous thromboembolism (VTE), including deep-vein thrombosis (DVT) and pulmonary embolism (PE), analyzing mortality associated with recurrent VTE or major bleeding is needed to determine the optimal duration of anticoagulation. This was a cohort study using the Registro Informatizado de Enfermedad TromboEmbólica (RIETE) Registry database to compare rates of fatal recurrent PE and fatal bleeding in cancer patients receiving anticoagulation for VTE. As of January 2013, 44, 794 patients were enrolled in RIETE, of whom 7911 (18%) had active cancer. During the course of anticoagulant therapy (mean, 181 ± 210 days), 178 cancer patients (4.3%) developed recurrent PE (5.5 per 100 patient-years; 95% CI: 4.8–6.4), 194 (4.7%) had recurrent DVT (6.2 per 100 patient-years; 95% confidence interval [CI]: 5.3–7.1), and 367 (8.9%) bled (11.3 per 100 patient-years; 95% CI: 10.2–12.5). Of 4125 patients initially presenting with PE, 43 (1.0%) died of recurrent PE and 45 (1.1%) of bleeding; of 3786 patients with DVT, 19 (0.5%) died of PE, and 55 (1.3%) of bleeding. During the first 3 months of anticoagulation, there were 59 (1.4%) fatal PE recurrences and 77 (1.9%) fatal bleeds. Beyond the third month, there were 3 fatal PE recurrences and 23 fatal bleeds. In RIETE cancer patients, the rate of fatal recurrent PE or fatal bleeding was much higher within the first 3 months of anticoagulation therapy.